Rh2(esp)2-Catalyzed Redox/Cycloaddition Cascade of Diazoacetoacetate Enones with N-Methyl Nitrones: Diastereoselective Synthesis of β-Lactams with Two Adjacent Chiral Centers - Zhao, Yingjun; Xu, Rujie; Xu, Zhengqing; Xu, Xichen (Synthesis, 2022)
A Rh2(esp)2-catalyzed diastereoselective synthesis of highly functionalized β-lactams is developed. By employing Rh2(esp)2 as the catalyst, a reaction cascade operates by reducing an N-methyl nitrone to the corresponding N-methyl imine in the presence of a first molecule of the diazoacetoacetate enone. A second molecule of the diazoacetoacetate enone sensing a change in the reaction medium undergoes a Wolff rearrangement to afford a vinyl ketene. This vinyl ketene then reacts with the in situ generated N-methyl imine to diastereoselectively furnish a β-lactam with two contiguous stereogenic centers. Extension of this method to the [2+2]-cycloaddition of PMB-protected imines and diazoacetoacetate enones catalyzed by Rh2(esp)2 is also reported.
Keywords: Rh2(esp)2; diazoacetoacetate enones; N-methyl nitrones; redox; β-lactams